2011
DOI: 10.1523/jneurosci.6322-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking Cortical Motor Output with Repetitive Microstimulation

Abstract: High frequency repetitive microstimulation has been widely used as a method of investigating the properties of cortical motor output. Despite its widespread use, few studies have investigated how activity evoked by high frequency stimulation may interact with the existing activity of cortical cells resulting from natural synaptic inputs. A reasonable assumption might be that the stimulus-evoked activity sums with the existing natural activity. However, another possibility is that the stimulus-evoked firing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 46 publications
(57 reference statements)
2
54
0
Order By: Relevance
“…Microstimulation in sensory cortical areas has a long and impressive history as a means of providing sensory information to the brain [61, 34, 62]. Microstimulation in motor areas rapidly causes a movement [63, 64, 65, 66, 67, 68]. We reasoned that microstimulation in sensory areas could be used to adjust an ongoing movement more rapidly than tactile stimulation, since microstimulation can bypass sensory transduction delays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microstimulation in sensory cortical areas has a long and impressive history as a means of providing sensory information to the brain [61, 34, 62]. Microstimulation in motor areas rapidly causes a movement [63, 64, 65, 66, 67, 68]. We reasoned that microstimulation in sensory areas could be used to adjust an ongoing movement more rapidly than tactile stimulation, since microstimulation can bypass sensory transduction delays.…”
Section: Discussionmentioning
confidence: 99%
“…As the perturbed network settles back into a more natural configuration of activity that is capable of influencing subsequent processes, eventually resulting in behavior. These concerns are exacerbated by the consideration that microstimulation must interact with ongoing neural activity, perhaps over-riding it [68], or combining with it in complex ways. Also in support of the notion that further cortical processing may be necessary to amplify and refine artificial signals, Horwitz and colleagues [72] elicited a behavioral response with optogenetic stimulation in primary visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the true ethological nature of the complex synergies evoked through DES was recently questioned by Cheney and colleagues. In monkeys, these authors provided evidence that postural synergies evoked through cortical stimulation were not produced by natural patterns of EMG activity but instead resulted from an unnatural co-contraction of numerous 'hijacked' muscles that forced the limb to an equilibrium point [74,75]. However, the generality of these observations remains debatable for at least three reasons.…”
Section: Mapping Complex Sensorimotor Synergiesmentioning
confidence: 99%
“…At the level of primary motor cortex, both intrinsic and extrinsic parameters may be represented (Kakei et al 1999), and extrinsic representations may take the form of preferred fragments of movement trajectories (Hatsopoulos and Amit 2012). Griffin et al (2011) showed that a 500-ms train of microstimulation to motor cortex can replace the high-level command for a certain target balance of muscle activity with a different one. These authors also suggested that low-level feedback loops in the complex spinal circuitry (reviewed by Arber 2012) may help to shape the time course of the electomyographic (EMG) activity as it progresses to the new target balance.…”
mentioning
confidence: 99%